Estudio de factibilidad para la industrialización de comida biológica para caninos domésticos en la ciudad de Bogotá (2017)
A feasibility study was made with the purpose of analyzing a new product in the market called ACBA/BARF, which happened in Bogotá. Oriented to the localities of Usaquén, Chapinero and Suba in the first semester of 2017, thought to be developed in the next 5 years, with the purpose of offering an alternative product for people who want to give their pets an organic product. Through the descriptive investigation used in the project answer to this questions was given: What? Who? Where? And How? That emerged during the realization of the project the existent variables and how they are related to each other. Thanks to the financial study it was posible to consolidate the required investment, the workforce needed to putt he project on track, thereforce, the required indicators were validated to show if the project is feasible and profitable; resultr were obtained, for example, an aopportunity internal rate of 25%, a VPN of $18.123.855 COP , a return internal rate of 34% with difference of 9% regarding to the TIO and a profit cost link of 1,239 this indicates that for each peso the investor gives, in return, the investor will receive 0,239.